Fast atom bombardment mass spectrometry of large peptides: A rapid method for molecular weight analysis - Bateman,A; Dell,A; Morris,HR (Journal of Applied Biochemistry, 1985)
A protocol which permits the molecular weight assignment of polypeptides in the 6000 to 8000-M(r) range has been developed. The procedure, which is based on the technologies of fast atom bombardment ionization and high field magnet mass spectrometry, has been applied to the semiroutine analysis of neurotoxins, including a scorpion toxin of unknown sequence. The type of instrumentation required for these studies is now widely available in mass spectrometry facilities which are readily accessible to the protein chemist. The results reported here indicate that fast atom bombardment mass spectrometry could greatly assist the rapid characterization of protein products of interest to biotechnologists.